School stress among Malaysian secondary school students: prevalence and demographic correlates - Tie-Seng Te; Hutkemri Zulnaidi; Norfaezah Md Khalid (International Journal of Evaluation and Research in Education (IJERE), 2026)
Understanding school stress is essential, given the significant time students spend in school and its impact on well-being. Acknowledging its importance, this study aimed to assess the level of school stress among Malaysian secondary school students. The respondents in this study consisted of 485 Malaysian secondary school students, selected through multistage sampling techniques to ensure national representativeness. Data were collected using a school-related stress questionnaire adapted from the shortened version of the adolescent stress questionnaire (ASQ-S). Data were analyzed using descriptive statistics, Rasch Wright mapping, independent samples t-tests for gender differences, and one-way ANOVA for grade and regional comparisons. The results indicated that, overall, Malaysian secondary school students experience low levels of school stress. Descriptively, female students reported higher levels of school stress than their male counterparts. Among different forms, Form 4 students reported the highest level of school stress, followed by Form 1 students. Regionally, students from the central and southern zones exhibited the highest levels of school stress. This study contributes to a better understanding of school stress among Malaysian secondary school students, providing insights for developing strategies to reduce stress in schools.